Occupational exposure to antineoplastic drugs in veterinary practice - Costa-Veiga, Ana (2018)
Handling cytotoxic drugs can imply the contamination of workplace surfaces and consequently workers exposure by dermal absorption. Mutagenicity, carcinogenicity, teratogenicity and acute side effects are linked to occupational exposure to these drugs. The growing demand for advanced treatments in companion animals increased the use of cytotoxic and immunosuppressive drugs in veterinary practice. Contrarily to human oncology, there are a small number of studies in veterinary oncology, therefore the aim of this study was to investigate the compliance rates of safety procedures in veterinary hospitals and clinics located in Lisbon that prepare and administrate cytotoxic therapies.